Peptide polymorphism under recommended dose of nitrogen fertilization in Brassica juncea: PEPTIDE POLYMORPHISM UNDER RECOMMENDED DOSE OF NITROGEN IN BRASSICA JUNCEA - IBANDALIN MAWLONG; REEMA RANI; M S SUJITH KUMAR; BASANT KUMAR KANDPAL; OM PRAKASH PREMI (Journal of Oilseeds Research, 2017)
Electrophoretically detectable seed storage proteins such as cruciferin, procruciferin and napin in mustard seeds possess the potential for taxonomic and evolutionary characterization of germplasm. This study was intended to see the genetic diversity among 24 genotypes of Indian mustard and the effect of N80 application on the protein profile. SDS-PAGE based profiles of seed proteins showed major differences in banding patterns among these genotypes. A total of eight peptide bands were assayed for their specificity in detecting genetic variability among Brassica genotypes under N0 and N80 conditions. Under N0 condition, a total of 166 bands (86.5%) were scored ranging from 10 kDa to 71 kDa in all genotypes, of which 118 showed polymorphic loci with 71.08 per cent polymorphism and similarity coefficient ranging from 0.375 to 1.0. Genotypes were clustered using UPGMA based clustering method into two major clusters. Cluster-I comprises of two cultivars, while cluster-II included the remaining twenty two cultivars. Under N80 condition, a range of 170 bands (88.5%) were found among 24 genotypes, of which 74 bands showed 38.5 per cent polymorphismwith similarity coefficient ranging from0.5 to 1.0. HB-9916 showed maximum variation (62.5%) in banding pattern of peptides with 3 per cent rise in polymorphism over N0 condition.